Synthesis, Characterization and Role of Zinc Oxide Nanoparticles in Wheat (Triticum indicum) Seeds Germination: Role of Zinc Oxide Nanoparticles in Wheat (Biological Sciences - PJSIR, 2022)
The current research was undertaken to examine the zinc oxide nanoparticles (ZnO NPs) effects on wheat (Triticum indicum) seeds germination and development. ZnO NPs were synthesized using co- precipitation method and their role in wheat seeds germination was determined. Prepared ZnO NPs were characterized using XRD, SEM, FTIR, UV-Visible spectroscopy. The particles crystallite determined by using XRD. SEM images showed size in range of 20 nm - 25 nm diameter. In vitro experiments of ZnO NPs at different concentrations (5 ppm, 10 ppm, 15 ppm and 20 ppm) were conducted to see the effects on germination of wheat seeds. The mortality rate of germinated wheat was decreased from 34% to 15% for control and 20 ppm samples of ZnO NPs, respectively. The root length was found to be increased from 82 mm, 88 mm, 89 mm and 90 mm for 5 ppm, 10 ppm, 15 ppm and 20 ppm respectively. Fresh weight was also increased from 2 g to 2.36 g, for 5 g to 20 g, respectively. All experiments were carried in triplicate. Growth of the plant i.e. the length of root and shoot enlarged significantly at 20 ppm. This study confirmed that crystallite ZnO NPs could be an alternate to available fertilizers.